Research Progress on the Microenvironment and Immunotherapy of Advanced Non-Small Cell Lung Cancer With Liver Metastases - Fang, Yujia; Su, Chunxia (Frontiers in Oncology, 2022)
Lung cancer is a malignant tumor with the highest morbidity and mortality, and more than 75% of patients are diagnosed at an advanced stage. Liver metastases occur in 20% of non-small cell lung cancer patients, and their prognosis are poor. In recent years, immune checkpoint inhibitor monotherapy and combination therapy have made breakthrough progress in advanced Non-small cell lung cancer (NSCLC) patients. However, compared with the overall population, the liver metastases population was an independent prognostic factor for poor immunotherapy response. Whether and how immunotherapy can work in NSCLC patients with liver metastases is a major and unresolved challenge. Although more and more data have been disclosed, the research progress of NSCLC liver metastasis is still limited. How liver metastasis modulates systemic antitumor immunity and the drug resistance mechanisms of the liver immune microenvironment have not been elucidated. We systematically focused on non-small cell lung cancer patients with liver metastases, reviewed and summarized their pathophysiological mechanisms, immune microenvironment characteristics, and optimization of immunotherapy strategies.